Design and implementation of broadband microwave amplifiers operating in the X band - Galicha, Rebecca C.; Molo, Carlos Virgil (2011)
Microwave amplifiers combine active elements with passive transmission line circuits to provide functions critical to microwave systems and instruments. Microwave Amplifiers are used for high power amplification at low microwave frequencies. It can amplify across broad spectrums of frequencies. They are suitable for use in broadband communication, instrumentation and electronic warfare applications. At lower bands, it is used primarily in mobile phones. In other bands, it is used in satellite communications. The range of frequency where it operates is 1 to 300 Ghz. For our design and implementation, the specifications given are operation on the Xband (8 to 12 Ghz). A more specific range of frequencies was suggested (11 to 11.5 GHz). Rebecca Galicha worked on the Cascaded, Reactively terminated single stage distributed amplifier topology and Carlos Molo worked on the Travelling Wave amplifier topology. Ansoft designer was used in the simulations. Gain flatness was also observed over the range of frequencies. Designs for both topologiesare unconditionally stable and s-parameter results are satisfactory. Fabrication for both designs was done in the laboratory and by an outside company. Outside fabrication was much better than fabrication in the laboratory as they have better equipment to suit the fabrication needs. Testing of the fabricated amplifier using the Vector Network Analyzer yielded unsatisfactory s-parameter results especially on the gain. Two separate tests were done on the fabricated designs. The first test was done on the old VNA and the second one was on the new and better VNA. Both yielded unsatisfactory results so it was concluded that the design of the amplifiers were not working. The proponents of the group recommended that the designs be revised for better results.
Undergraduate student project (B.S. Electronics and Communications Engineering)--University of the Philippines, Diliman.
Keywords: Microwave amplifiers -- Design and construction